Operative Versus Non-Operative Treatment of Severely Shortened or Comminuted Clavicle Fractures in Older Adolescent Athletes: Results from A Prospective, Multicenter, Level 2 Cohort Study. Issue 7 (30th July 2021) - Wilson, Philip; Bae, Donald; Busch, Michael; Edmonds, Eric; Ellis, Henry; Hergott, Katelyn; Kocher, Mininder; Li, G. Ying; Liotta, Elizabeth; Nepple, Jeffrey; Pandya, Nirav; Pennock, Andrew; et al.
Objectives: Operative management of clavicle fractures is increasingly advocated for athletes and young adults. Surgical indications and optimal treatment for comminuted or severely shortened clavicle fractures in adolescent athletes remain unclear. The purpose of this study was to evaluate the outcomes of non-operatively and operatively treated comminuted and/or severely shortened (>25mm) clavicle fractures in older adolescent athletes. Methods: Athletes aged 14 to 18 years with mid-shaft clavicle fractures who had non-operative (NONOP) or operative (OP) treatment at one of eight participating centers between 2013 and 2017 were screened for the presence of comminution and/or fracture shortening >25mm. Demographics, injury mechanism, fracture characteristics and treatment (NONOP vs. OP) were prospectively recorded and patients followed for a minimum of two years. Complications, rates and timing of return to sport (RTS), and patient reported outcomes (PROs: ASES, QuickDASH, MARX shoulder activity, EQ-5D, EQ-VAS, and patient satisfaction) were analyzed. Results: The two groups included 137 patients (70 NONOP, 67 OP), with a similar distribution among various sports—most commonly football—and rates of competitive athletic participation (NONOP: 81%, OP: 85%) (Figure 1). Of the 137 patients, 100 [NONOP n=52, 15.3 years, 44 males (84.6%); OP n= 48, 15.5 years, 40 males (83.3%)] provided PROs at> 2 years. Comminution (C) and shortening (S) were not different between groups [NONOP C=24 (46.2%), S=28mm (24.5, 33.2); OP C=35 (72.9%), S=28mm (25.0, 36.5)], but the OP group demonstrated 3 mm greater vertical displacement [NONOP 13.0 (9.6, 18.0) mm, OP 16.0 (11.8, 21.0) mm; p<0.05], which was therefore controlled for as a statistical confounder in the comparative PRO analysis. There was no difference in nonunion, delayed union, symptomatic malunion, re-fracture, or clinically significant complications between treatment groups (Table 1). Two years after injury, 75% of NONOP and 79% of OP patients reported RTS, with 61% and 57%, respectively, reporting achievement of same sport-level and similar RTS timing (OP=10 weeks, NONOP= 11.6 weeks). When controlling for minor differences in superior displacement, regression and matching analyses demonstrated no difference in mean and dichotomized PRO scores between the NONOP and OP groups (Table 2). Conclusions: In this prospective multi-center cohort of comminuted and/or severely shortened (>25mm) clavicle fractures in adolescent athletes, there was no difference in complications, RTS, or PROs between non-operatively and operatively treated patients at 2 years. Despite several studies suggesting the contrary in adult populations, comparably excellent outcomes of severe clavicle fractures in adolescent athletes can be achieved with non-operative treatment.